Anticancer potential of dihydrocaffeic acid: a chlorogenic acid metabolite. Issue 1 (1st January 2020) - Santana-Gálvez, Jesús; Villela Castrejón, Javier; Serna-Saldívar, Sergio O.; Jacobo-Velázquez, Daniel A.
ABSTRACT: Chlorogenic acid is a well-known nutraceutical, but it is extensively metabolized by the body. More valuable information can be obtained from its metabolites. Dihydrocaffeic acid is a metabolite of chlorogenic acid and has shown antioxidant, cardioprotective, and neuroprotective effects; however, information about its anticancer activity is very scarce. Therefore, the main objective of this study was to determine the anticancer potential of dihydrocaffeic acid. The cancer cell lines used were MCF-7, Hep-G2, PC-3, and HCT-116, while HDFa was used as healthy cells. The cytotoxic concentrations to kill 50%, 75%, and 90% of the cells (CC50, CC75, CC90 ) were determined using the MTS assay. Dihydrocaffeic acid was significantly more cytotoxic for most cancer cell lines, including MCF-7, PC-3, and HCT-116, compared with HDFa; however, Hep-G2 was significantly more resistant than HDFa. Dihydrocaffeic acid is a potential candidate for cancer prevention and treatment. The mechanism of action remains to be elucidated.